Integrated environmental risk assessment of rare earth elements mixture on aquatic ecosystems - Lachaux, Nicolas; Cossu-Leguille, Carole; Poirier, Laurence; Gross, Elisabeth Maria; Giamberini, Laure (Frontiers in Environmental Science, 2022)
In the last decades, rare earth elements (REE) became essential in strategical sectors such as high- and green-technologies. Their increasing use in human activities worldwide lead to anthropogenic REE releases detectable in all compartments of the environment transforming REE into emerging contaminants. However, their potential impacts on ecosystems are still poorly understood. In order to have a comprehensive understanding of REE ecotoxicology and to assess properly their environmental risk, we analysed the toxicity of three representative REE (neodymium Nd, gadolinium Gd, and ytterbium Yb). Following recommendations of the European Chemicals Agency, we assessed REE hazard by performing standard ecotoxicological tests on three freshwater species belonging to different trophic levels (algae, crustacean and fish). EC50 were calculated using different modes of expression of REE exposure concentration (based on nominal, measured total and dissolved concentrations) in order to determine more properly and accurately REE toxicity. In order to get closer to environmental conditions, we also tested the toxicity of REE in mixture because all of them occur naturally as such in the environment. Moreover, we added dissolved organic matter (DOM) in the test medium because DOM is ubiquitous and drives REE speciation in freshwater systems. Results show that DOM significantly reduced REE bioaccumulation and toxicity probably by formation of non-bioavailable REE-DOM complexes. The algal species was the most sensitive to REE. Despite slight differences between Nd, Gd and Yb concerning their behaviour and bioaccumulation, the three REE exhibited comparable toxicity and additive effects in mixture to all organisms tested. Thus, for the first time, we assessed the environmental risk of REE in freshwater based on mixture toxicity (instead of using single element toxicity) considering REE as a uniform group. Comparison of REE hazard concentrations with REE concentrations measured in different environmental scenarios revealed that risks are currently limited to REE from wastewater treatment plant, industrial and mining activities, whose released quantities can induce severe damages towards exposed freshwater organisms. However, REE risks are likely to be more widespread in the future because of expected increasing anthropogenic REE releases.